2018
DOI: 10.1213/ane.0000000000002418
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Patients Undergoing Cardiac Surgery Who Decline Transfusion and Received Erythropoietin Compared to Patients Who Did Not: A Matched Cohort Study

Abstract: In this retrospective matched cohort study of patients declining transfusion and receiving EPO matched to control patients, there were no clinically meaningful differences in the outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 24 publications
2
34
0
1
Order By: Relevance
“…Other factors that have been studied with regard to infectious risk and central line placement include site of line placement (internal jugular vein versus subclavian vein), type of catheter used (subcutaneous port versus tunneled central access devices), and the age of patient. 15,28,29,32 In keeping with the literature, we found that the choice of vessel (internal jugular vein versus subclavian vein) did not influence infectious risk. Prior studies found an increased risk of infectious complications following line placement in children less than 10 years of age.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Other factors that have been studied with regard to infectious risk and central line placement include site of line placement (internal jugular vein versus subclavian vein), type of catheter used (subcutaneous port versus tunneled central access devices), and the age of patient. 15,28,29,32 In keeping with the literature, we found that the choice of vessel (internal jugular vein versus subclavian vein) did not influence infectious risk. Prior studies found an increased risk of infectious complications following line placement in children less than 10 years of age.…”
Section: Discussionsupporting
confidence: 84%
“…It is hypothesized to be secondary to the release of cytokines from leukemic cells, the administration of certain drugs, or even the transfusion of blood products. 32 While fever in an oncology patient is often multifactorial, and may not be an indication of acute infection, it has been found to be associated with a higher rate of post-operative infections following SQP insertion. 2 Similarly, our study demonstrated a significantly increased risk of infection following SQP placement in patients that had a documented fever in the 24 hours preceding surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The renoprotective and anti-inflammatory properties of EPO are controversial. The perioperative use of EPO in the prevention and treatment of postoperative AKI has only been studied in cardiovascular surgery with conflicting results [ 106 , 107 , 108 ]. The impact of ANP and EPO on AKI prevention in major abdominal surgery patients has not been studied.…”
Section: Managementmentioning
confidence: 99%
“…The study noted that there were no clinically significant differences in outcomes measured between the two cohorts, demonstrating the positive impact of EPO for patients refusing transfusion and hence supports its use for Witness patients. 8 Eleven comparative studies discussing outcomes between Witnesses and non-Witnesses were found 2,16,21,[45][46][47][48][49][50][51][52] (Table 2) and these often gave agents to increase the preoperative Hb. This varied between studies and makes comparison more challenging.…”
Section: Pre-operativementioning
confidence: 99%